Estimasi Sumberdaya Andesit dan Breksi Piroklastik Sebagai Bahan Konstruksi PT. Tepat Guna Referindo Lombok Timur: Estimation of Andesite and Pyroclastic Breccia Resources as Construction Materials for PT. Tepat Guna Referindo East Lombok - Rukayah, Rukayah; Syailendr, Aji; Erintina, Melinda Dwi (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2024)
Estimate of andesite and pyroclastic breccia resources at PT Tepat Guna Reforindo has been carried out. Which is an area with potential for non-metallic mining materials. This research was carried out using the Civil 3D Gridding method. One of the non-metallic minerals found in East Lombok district is andesite rock and pyroclastic breccia. The research was carried out using petrological analysis methods to obtain rock types and estimate the availability of minerals and sieve analysis to obtain density values at the research location. Based on the results of petrological analysis, it shows that the sample is a type of andesite rock and also breccia. However, the presence of all samples is dominated by andesite rock samples which are abundant in 95% of the exploration area. Based on the results estimation of andesite rock resources from geological modeling and calculations using the Civil 3D Gridding method from A-B at an elevation of 100-40 meters above sea level, it was found that the measured resource of andesite rock units had a volume of 492,638.108 m3 and resource of pyroclastic breccia rock units had a volume of 738,957.162 m3, results of the analysis of the average rock density of 2.74 g/cm3, then the tonnage of the andesite unit is 1,302,781.480 tons and the pyroclastic breccia tonnage is 1,998,879.120 tons.